2023
DOI: 10.1039/d3tc01136d
|View full text |Cite
|
Sign up to set email alerts
|

A highly stretchable and sensitive strain sensor for lip-reading extraction and speech recognition

Abstract: Speech recognition often relies on visual stereo images and videos, but it is often limited by light intensity and opaque occlusions such as mask (the coronavirus disease 2019 (COVID-19) pandemic)....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The sensors were also attached to the upper edge of the eyebrows (Figure f) to detect the inward and upward movement of the eyebrow for “anger” and “wonder”, respectively, and also on the cheeks (Figure g) for different expressions such as “wonder” and “smile”. The sensitivity of 5ZSS allows distinguishing all the five vowels characteristic as well as characteristic facial expressions ranging 2 < Δ R / R 0 < 40, much better than conventional face recognition research limited a much smaller range, Δ R / R 0 < 10. ,, Our strategy enables high performance designs and shows significant potential for practical applications in implantable soft electrodes, electrophysiological signals on the body surface, and smart sensors, paving the way for the advancement of future robotics.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The sensors were also attached to the upper edge of the eyebrows (Figure f) to detect the inward and upward movement of the eyebrow for “anger” and “wonder”, respectively, and also on the cheeks (Figure g) for different expressions such as “wonder” and “smile”. The sensitivity of 5ZSS allows distinguishing all the five vowels characteristic as well as characteristic facial expressions ranging 2 < Δ R / R 0 < 40, much better than conventional face recognition research limited a much smaller range, Δ R / R 0 < 10. ,, Our strategy enables high performance designs and shows significant potential for practical applications in implantable soft electrodes, electrophysiological signals on the body surface, and smart sensors, paving the way for the advancement of future robotics.…”
Section: Resultsmentioning
confidence: 96%
“…Another application that requires high sensitivity for 5–10% of the strain range is the recording of signals from facial muscle movements. Earlier studies identified vowels that are essential units in speech and emotions such as smiling or anger, both through facial skin movements. Our 5ZSS was applied to three areas of the face prone to experiencing most strain to measure vowel speech and facial expressions. The signals of the mouth were recorded in real time during the vocalization of “O”, “U”, “A”, “I”, and “E”.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This attribute renders it valuable for applications demanding a high degree of stretchability. 28,49,50 Consequently, a hybrid material combining PMHS and VTMS can yield a highly elastic substance that exhibits substantial deformation under stress.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, wearable glucose monitors provide non-invasive blood glucose monitoring for people with diabetes, reducing the need for frequent finger-stick tests and providing real-time data for better management. From early forms such as smartwatches to cutting-edge developments in flexible electrodes, wearable technologies continue to evolve, promising a future with innovative applications [13].…”
Section: Evolution Of Smart Wearable Devicesmentioning
confidence: 99%